Nova abordagem laboratorial na investigação das Enteroparasitoses em humanos - Souza, Patrícia Xavier de (2005)
A study was carried out in order to estabilish a protocol for intestinal human parasitic diagnosis using a study of prevalence of parasitic infections including analisis of sanitary conditions, among the poor community of Jóquei, a district of São Gonçalo, RJ. Stool specimens were collected from 188 subjects selected by chance whom agreeded in their participation in the study. The stool specimens were collected in labeled plastic vials with 10% buffered formaldehyde and processed by the standardized Coprotest method. The sediments with questionable morphology of the protozoan were dived in the SAF fixative and submitted to the trichrome stain and iron haematoxilin simplified. The fecal material sediment from children between 1 and 5 years old were all stained with safranin-methylene blue for the investigation of the intestinal coccidial. The global prevalency of enteroparasitosis was 46% of the researched population, where 53% were found infected by more than one species. The more frequents parasites were: Entamoeba coli (14%), Ascaris lumbricoides (13%), Entamoeba histolytica/Entamoeba dispar (11%) e Blastocistis hominis (9%). Therefore, no cocidiose case was found in the population between 1 and 5 years old, age group where these parasites are usually more found. The high prevalence found in this study can be explained by the low socio-economic and environmental conditions in the community. A chi-square analysis showed that Entamoeba coli, Entamoeba histolytica / Entamoeba dispar and Ascaris lumbricoides infections were significantly higher in males than females. In this current study most of the complaints by the study population: colic (22%) and diarrhea (16%) were related with intestinal parasitic infection. Age group 0 10 years old had the highest prevalence to Giardia lamblia possible due to poor sanitary and low immunity. All of the stool samples examined that presented questionable Lugol temporary stain were confirmed by trichrome stain and iron hematoxilin modified, showing the importance of its use in the detection and identification of intestinal parasites. The fecal sediment of Coprotest method also was stained with safranin methylene blue and was efficient to identify Cryptosporidium sp.. Hence, the proposed protocol enables a confiable study of intestinal parasites prevalence in the estudied community